Mechanisms of Structure and Thermoelectric Properties of Vapor-Phase Condensates Solid Solution PbTe–Bi2Te3 on Ceramics - Bylina, I. S. (Physics and Chemistry of Solid State, 2015)
Based on analysis of AFM-images, presents the results of complex research the mechanisms of nucleation and growth processes, surface topology and thermoelectric properties of vapor-phase condensates PbTe-Bi2Te3, grown on polycrystalline ceramics at constant temperatures evaporation TE = 970 K and deposition TS = 470 K. Deposition time τ = (15-75) s, and the percentage of Bi2Te3 was 1-5 mol.%. The dependence of structural characteristics (average size of nanocrystals, their rate of change in the lateral (Dc, Dc/τ) and normal (hc, hc/τ) directions to the substrate surface) and thermoelectric parameters (electrical conductivity (σ), Hall concentration (n) and mobility media (μ) thermo-EMF (S) and thermoelectric power (S2σ)) condensates PbTe–Bi2Te3 the conditions of their receipt.